Assessment of post-pandemic NAAT-based diagnostic capacity among laboratories with COVID-19 testing resource investments in Indonesia - Bony Wiem Lestari; Almira Alifia; Putu Wahyuni Wulandari Karnawati; Nurlaila Syahri Ramadhani; Selvia Kusdwiyanti; Nurholis Majid; Ryan Bayusantika Ristandi; Rifky Waluyajati Rachman; Philip C. Hill (PLoS ONE, 2026)
Background Throughout COVID-19 pandemic, many countries expanded their diagnostic infrastructure, including Indonesia. West Java, one of the most COVID-19-affected provinces in Indonesia, received many PCR machines during the pandemic but the molecular diagnostic landscape left post-pandemic needs to be assessed to build an improved pandemic preparedness in the area and enhance control of other diseases. Aims To evaluate the post-pandemic diagnostic capacity of district health laboratories (DHLs) in West Java, to determine factors associated with laboratories’ performance capacities and to portray its DHLs’ diagnostic profiles to explore the possibility of implementing an additional NAAT-based tuberculosis test in the province. Methods This was a cross-sectional laboratory survey, assessing 26 DHLs in West Java, Indonesia. Data were collected through direct visits, interviews based on questionnaire based on WHO Laboratory Assessment Tool, and focus group discussion. The questionnaire was then quantitatively scored and used to categorize capacity levels as strong (>=85%), good (70–84%), weak (50–69%), or very weak (<50%). Descriptive statistics were also used to highlight key gaps. Results Out of 26 DHLs, only 34.6% had strong NAAT-based diagnostic capacity, 34.6% had good capacity, while 30.8% were categorized as weak or lower. 80.8% of the DHLs scored weak or very weak in ‘Laboratory Testing Performance’ module, and only 11.5% of DHLs conducted PCR machine calibration in the past year. Only 46.2% maintained a functional BSL-2 laboratory, and the median of PCR-trained staff was 2 (IQR 1–4), with 15.4% DHLs no longer retaining any biomolecular staff. Conclusion The sustainability of COVID-19 diagnostic investments post-pandemic is relatively poor across many districts in West Java. Commitment to sustain facilities and equipment, as well as to retain an adequate workforce, is warranted to strengthen pandemic preparedness in the area and to repurpose COVID-19 facilities for tuberculosis control purposes.